PERSEPSI GURU TAMAN KANAK-KANAK TERHADAP PEMBELAJARAN MATEMATIKA DI KECAMATAN SIAK HULU KABUPATEN KAMPAR - Saragih, Ince Natalia; Solfiah, Yeni; ,, Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract : This study aims to determine the perception of kindergarten teachers towards mathematicslearning in Siak Hulu District, Kampar Regency. This study uses a quantitative descriptive approach. Theresults of this study can be concluded into a good category. The overall perception of teachers about earlychildhood learning creativity is said to be good in several indicators of creativity, namely creativity of fluencyof thinking obtaining an average of 72.875, creativity of flexibility of thinking obtaining an average of 70.93,creativity of elaboration of thinking obtaining an average of 71, and creativity of originality of thinkingobtaining an average of 70.16. Of the four indicators of creativity, there is an indicator that obtains thehighest average result of 72.875, namely creativity of fluency of thinking, and it can be seen overall that thefour indicators of creativity reach a percentage of 60 - 79 which is interpreted as good. When viewed basedon the results of the research of each of the eight research subjects, the researcher describes the mostprominent results of teacher perceptions, namely research subject A6 who obtained an overall average resultof 9.6 and is interpreted as very good. This is influenced by the length of work period, which is 5 years, ofcourse the teacher already has various experiences and additional knowledge about early childhoodlearning. While the results of the perception that are not so prominent but are still in the very good categoryare research subject A8, namely obtaining an overall average result of 8.31. This is influenced by the lengthof work period which is still new, which is 4 months running.Key Word : Teacher Perception, Learning